Implementasi Tiga Kata Ajaib Bagi Pembentukan Karakter Kristen Anak Generasi Alpha - Gulo, Kristov; Santosa, Monica (JURNAL DIAKONIA, 2024)
This research aims to describe the three magic words in the character building of Alpha generation children. The reluctance of a child who is lazy to interact with other people in his environment apparently makes the child lose the opportunity to find and grow the character that exists in him. In researching, the author uses a descriptive qualitative research method of literature review. The three magic words are words that have different meanings, where these three words are needed in building a relationship or relationship with other people in the neighborhood. For this reason, the formation of the Christian character of alpha generation children must be done early, so that the mentality of each child can be educated and formed into a quality and moral character, as in Christian teachings that imitate Jesus Christ as a person of character. Therefore, the formation of Christian character of alpha generation children starting early is the first step to building a good personality.